PEMIKIRAN FRIEDRICH NIETZSCHE: TUHAN TELAH MATI DAN IMPLIKASINYA BAGI PENDIDIKAN AGAMA KRISTEN - Yohanis Pandie, Remegises Danial (The Way: Jurnal Teologi dan Kependidikan, 2024)
This article aims to analyze Friedrich Nietzche's thoughts on God is dead. Nietzche said that humans have killed God with attitudes and behaviors that do not reflect the life of Jesus.Nietzsche's critique goes beyond simply acknowledging the absence of God; it confronts the implications of the absence of human existence. He argues that the death of God necessitates a radical reassessment of values, since the moral framework that has governed society is no longer tenable. In the context of Christian education, Nietzsche's assertion calls for a reassessment of the pedagogical approaches used in teaching religious concepts. However, many authors consider Nietzche's criticism as a form of rebellion and denigration of Christianity. The research method used is a literature study. The results of the study show that Nietzche's criticism contributes to thinking related to critical thinking, multicultural education and the development of Christian educators' abilities in implementing each learning, so that Christian doctrinal fascism does not occur. Nietzsche's statement about the death of God presents both challenges and opportunities for Christian religious education.